Analysis of Factors Influencing Self-Medication Behavior - Andry Christian; Waluyo Budi Atmoko; Sugiyarmasto Sugiyarmasto (Westscience Press, 2026)
Self-medication is a practice of self-treatment that is increasingly common among the public as a response to limited access to health services, high medical costs, and the ease of obtaining medicines without a doctor's prescription. This study aims to analyze the factors that influence self-medication behavior, including knowledge, medical costs, drug advertisements, previous medical experiences, and advice from others. The research approach uses a quantitative method with a survey design. Data were collected through questionnaires from 219 respondents who had purchased drugs without a doctor's prescription, using purposive sampling techniques. Data analysis was performed using binary logistic regression. The results showed that all independent variables simultaneously had a significant effect on self-medication behavior. Partially, knowledge, medical costs, drug advertisements, previous medical experiences, and advice from others were proven to have a positive and significant effect on an individual's tendency to self-medicate. The research model has excellent predictive ability with an accuracy value of 91.8% and a Nagelkerke R Square value of 78.6%. These findings indicate that self-medication behavior is influenced by a combination of personal, economic, informational, and social factors. Therefore, continuous educational efforts and strengthening of regulations related to the use and promotion of drugs are needed to encourage safer and more responsible self-medication practices.